2018
DOI: 10.31557/apjcp.2018.19.12.3581
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase II α Gene alteration in Triple Negative Breast Cancer and Its Predictive Role for Anthracycline-Based Chemotherapy (Egyptian NCI Patients)

Abstract: Objective: Triple negative breast cancer is an aggressive variant of breast cancer; it forms about 15% of breast cancer cases. It lacks the responsiveness to hormonal and targeted therapies. Anthracyclines remain the treatment option for these patients. Anthracyclines are cardiotoxic, so predicting sensitivity of response by biological predictors may have a role in selecting suitable candidates for these drugs. Material and methods: This study included 50 TNBC cases, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…TOP2A can be used as a potential biomarker to predict the prognosis of patients with malignant tumors and screen out high-risk cases in order to enable individualized treatment ( 21 ). In a study on triple-negative breast cancer, a significant association was observed between the TOP2A gene and chromosome 17 polysomy (CEP17) status, and TOP2A has a certain predictive effect on the therapeutic effect of anthracycline drugs ( 22 ). Wittmann et al ( 23 ) confirmed that the high expression of TOP2A was associated with tumor metastasis and death outcome by analyzing 102 cases of nephroblastoma.…”
Section: Introductionmentioning
confidence: 99%
“…TOP2A can be used as a potential biomarker to predict the prognosis of patients with malignant tumors and screen out high-risk cases in order to enable individualized treatment ( 21 ). In a study on triple-negative breast cancer, a significant association was observed between the TOP2A gene and chromosome 17 polysomy (CEP17) status, and TOP2A has a certain predictive effect on the therapeutic effect of anthracycline drugs ( 22 ). Wittmann et al ( 23 ) confirmed that the high expression of TOP2A was associated with tumor metastasis and death outcome by analyzing 102 cases of nephroblastoma.…”
Section: Introductionmentioning
confidence: 99%
“… 32 It has been reported that this topoisomerase could function as a target for anti-cancer therapy, and a variety of mutations in this gene are associated with the development of drug resistance. 33 - 35 Moreover, TOP2A is commonly amplified in thyroid cancer according to the COSMIC and cBioPortal databases, and the mutational frequency is approximately 1%. CDC20 encodes a protein that acts as a regulatory factor for multiple mitotic processes 36 ; this protein has been reported in various malignancies and plays a vital role in tumorigenesis and progression.…”
Section: Discussionmentioning
confidence: 99%
“…showed that TOP2A played a predictive role for anthracycline-based chemotherapy [37]. CCNB1, known as cyclin B1, is a highly conserved cyclin.…”
Section: Discussionmentioning
confidence: 99%